Między (re)konstrukcją a nostalgią. Współczesny polski i rosyjski neopoganizm w kontekście „postcolonial studies” - Nakoneczny, Tomasz (Studia Rossica Posnaniensia, 2019)
The article proposes a look at contemporary neopoganism as a phenomenon that can be described in the context of postcolonial studies. However, analyzing neopaganism through the prism of the classic postcolonial terms seems to be insufficient to the author. Therefore, he proposes to supplement it with the concept of nostalgia. He also disagrees with the view that neopaganism is the part of the postmodern trend of contemporary culture.